Implementation of digital sigma-delta modulators for high-resolution audio digital-to-analog converters based on field programmable gate array - Zbigniew KULKA; Piotr WOSZCZEK (Archives of Acoustics, 2014)
Sigma-delta modulators (SDMs) are now widely used in high-resolution audio analog-to-digital converters (ADCs) and digital-to-analog converters (DACs). The field programmable gate array (FPGA)-based hardware is particularly suitable for the implementation of basic functional blocks of audio sigma-delta DACs. This paper presents the design, simulation, and the FPGA implementation of the lowpass digital sigma-delta modulators (SDMs) in various configurations. The results can be used for digital SDM designs and its future applications in the audio sigma-delta DACs as well as for educational purposes.